Exercise‐induced changes in cardiovascular function after stroke: a randomized controlled trial. Issue 7 (22nd October 2013) - Tang, Ada; Eng, Janice J.; Krassioukov, Andrei V.; Madden, Kenneth M.; Mohammadi, Azam; Tsang, Michael Y. C.; Tsang, Teresa S. M.
<x xml:space="preserve">Abstract</x> Background and aims Cardiovascular co‐morbidities are prevalent after stroke, with heart disease, hypertension and impaired glucose tolerance present in the majority of cases. Exercise has the potential to mediate cardiovascular risk factors commonly present in people with stroke. This single‐blinded randomized controlled trial compared the effects of high versus low intensity exercise on fitness, cardiovascular risk factors, and cardiac function after stroke. Methods Fifty participants (age 50–80 y, >1 y post‐stroke) were randomized to a high‐intensity Aerobic Exercise (AE) or low‐intensity non‐aerobic Balance/Flexibility (BF) program (6 months, 3 60‐min sessions/week). Outcomes assessed by VO2peak (primary outcome), arterial stiffness, ambulatory capacity, hemodynamics and cardiac function using echocardiography, and lipid, glucose and homocysteine levels. Assessors were blinded to group allocation. Results Twenty‐three (92%) of 25 AE group participants (withdrawals unrelated to the intervention) and all BF group participants completed the program. One BF group participant experienced 2 non‐injurious falls during class. No other adverse events occurred. There were no changes in VO2peak in either group (AE 16·9 ± 7 to 17·4 ± 7 ml●kg−1●min−1 vs. BF 16·9 ± 6 to 16·6 ± 5 ml●kg−1●min−1, P = 0·45), but AE group demonstrated greater improvement in right atrial emptying fraction (AE 30 ± 22 to 37 ± 22% vs. BF 35 ± 20 to 31 ± 20%, P = 0·04). Both groups demonstrated improvements in lipid profiles, glucose and homocysteine levels, and ambulatory capacity (P < 0·04). Conclusions This was the first study to examine the effects of aerobic exercise after stroke on cardiovascular hemodynamics. High‐intensity exercise improved right‐sided function and early myocardial relaxation. Low‐intensity exercise may also benefit plasma lipid, glucose and inflammatory markers, and ambulatory capacity. This study is an important step towards understanding mechanisms by which exercise may reduce cardiovascular risk and function.